2016 Global food policy report survey - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
Over 1,000 individuals representing more than 80 countries responded to a Global Food Policy Report survey on perceptions about food policy and food security now and for the future, and on priorities among the Sustainable Development Goals. The respondents, most of whom work in agricultural or economic development, or the health and nutrition field, are pessimistic about the possibility of eliminating hunger and undernutrition by 2025 globally. They are more optimistic, however, about eliminating hunger and undernutrition in their own countries. Among the 17 Sustainable Development Goals, most respondents give priority to ending hunger.